2021
DOI: 10.2217/bmm-2021-0348
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mirnas As Biomarkers of Covid-19: A Scoping Review of the Status and Future Directions for Research in This Field

Abstract: Aim: miRNAs are potential biomarkers of several diseases. This review aimed to identify the miRNAs that could serve as biomarkers of COVID-19. Materials & methods: A literature search of nine databases was carried out for studies published before 13 June 2021 that described dysregulated miRNAs in cells or animals infected by SARS-CoV-2 or in patients with COVID-19. Two independent reviewers selected the studies and extracted data; disagreements were resolved by a third reviewer. Results: Twenty studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…We also highlighted a significant time-dependent change in miR-155-5p and SOCS1 levels during COVID-19. Among miRNAs, circulating miR-155 (down-regulated or up-regulated) has been considered one of the most promising diagnostic and predictive biomarkers of COVID-19 [ 25 ]. In contrast to the literature and our findings, a recent study found reduced expression levels of miR-155 in the serum of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…We also highlighted a significant time-dependent change in miR-155-5p and SOCS1 levels during COVID-19. Among miRNAs, circulating miR-155 (down-regulated or up-regulated) has been considered one of the most promising diagnostic and predictive biomarkers of COVID-19 [ 25 ]. In contrast to the literature and our findings, a recent study found reduced expression levels of miR-155 in the serum of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that miRNAs were significantly dysregulated in COVID-19 [ 75 ]. The most important miRNAs that can be used as COVID-19 biomarkers are miR-21-5p, miR-144, and miR-155 [ 75 ]. miRNA-146a can be used as a biomarker for the severity of COVID-19 [ 75 ].…”
Section: Changes In Mrna Expression—mirna ‘’Silencing’’ Interferencementioning
confidence: 99%
“…The most important miRNAs that can be used as COVID-19 biomarkers are miR-21-5p, miR-144, and miR-155 [ 75 ]. miRNA-146a can be used as a biomarker for the severity of COVID-19 [ 75 ].…”
Section: Changes In Mrna Expression—mirna ‘’Silencing’’ Interferencementioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) is the clinical manifestation of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [ 1 ]. This infection started to spread across the world in 2019, increasing hospitalization rates in several countries, and rapidly turned into a global pandemic [ 2 ]. Considering the high infection rate, which can affect an elevated percentage of individuals in each community in a short period, the mortality rate and the death risk estimation are related to the breakdown of the healthcare systems [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the high infection rate, which can affect an elevated percentage of individuals in each community in a short period, the mortality rate and the death risk estimation are related to the breakdown of the healthcare systems [ 3 , 4 ]. Therefore, on March 2020, the World Health Organization (WHO) declared a pandemic, leading to the emergence of public health strategies to contain the outbreak, including social confinement and movement restriction [ 2 , 5 ]. Reported illnesses have ranged from very mild (including some with no reported symptoms) to severe, including illness resulting in death [ 4 ].…”
Section: Introductionmentioning
confidence: 99%